Origin of the silicic volcanic rocks of the Early Permian Panjal Traps, Kashmir, India - Shellnutt, J. Gregory; Bhat, Ghulam M.; Wang, Kuo-Lung; Brookfield, Michael E.; Dostal, Jaroslav; Jahn, Bor-Ming (Chemical geology, 2012)
The Panjal Traps of Kashmir, India represent a significant outpouring of mafic and silicic volcanic rocks during the Early Permian and are synchronous with the opening of the Neotethys Ocean. Previous studies have suggested that the silicic volcanic rocks are derived by differentiation of mafic magmas. Dacites and rhyolites collected from the lower portions of the volcanic pile near Pampore, Kashmir are peraluminous (ANCK>1.0) in composition. Their calculated whole rock ISr values are variable (ISr=0.69307 to 0.71825) and indicate open system behavior of either Rb or Sr or both whereas their Nd isotope compositions (εNd(T)=−8.6 to−8.9) are nearly uniform. The εNd(T) values and trace element (Th/NbPM>4; Nb/U<10; Th/Ta>8) ratios suggest the rocks are derived partially or wholly from the crust. Least squares and MELTS modeling indicate that the likely source of the silicic rocks is the middle crust rather than the lower or upper crust. Furthermore, the silicic Panjal Traps have trace element compositions similar to some felsic volcanic rocks and A-type granitic rocks from other large igneous provinces (e.g. Karoo, Parana and CAMP). The Paleoproterozoic TDM ages (TDM=1836 to 1937Ma) indicate that the rocks were likely derived from an ancient crustal source which experienced multiple episodes of recycling. In contrast to silicic volcanic rocks from other LIPs, the silicic Panjal Traps are unusual in that they did not involve mantle source material. The heat required to melt the crust was likely due to the continuous injection of contemporaneous basaltic magmas which formed the majority of the mafic Panjal Traps. [Display omitted] ► Dacites and rhyolites are found within the lower flows of the Panjal Traps. ► The silicic Panjal Traps are derived by partial melting of ancient sialic crust. ► The silicic rocks are compositionally similar to peraluminous ‘A-type’ granites. ► The Early Permian Panjal Traps are related to the opening of the Neotethys Ocean.